Novel association of Psychrobacter and Pseudomonas with malodour in bloodhound dogs, and the effects of a topical product composed of essential oils and plant‐derived essential fatty acids in a randomized, blinded, placebo‐controlled study. Issue 6 (24th September 2018) - Meason‐Smith, Courtney; Older, Caitlin E.; Ocana, Roxanna; Dominguez, Brandon; Lawhon, Sara D.; Wu, Jing; Patterson, Adam P.; Rodrigues Hoffmann, Aline
Abstract : Background: The pathogenesis and treatment of cutaneous malodour in dogs have not been investigated previously. Staphylococcus and Corynebacterium spp. are associated with human axillary malodour. Hypothesis: Staphylococcus and Corynebacterium spp. are associated with cutaneous malodour in dogs, and treatment with a topical essential oil‐based product will improve malodour and reduce the abundance of odour‐causing bacteria. Animals: Twenty seven bloodhound dogs from a south Texas boarding facility were enrolled in this study. Methods and materials: Skin swabs were taken from the axilla and dorsum of 27 dogs at initiation of the study. Mean malodour scores were used to assign dogs to control or malodour groups. The malodourous dogs were randomly assigned to a treatment or placebo group, received four weekly topical applications of the spot‐on or placebo, and samples were recollected. Next‐generation sequencing (NGS) and real‐time quantitative PCR (qPCR) were performed on all swabs. Results: Psychrobacter and Pseudomonas spp. were significantly more abundant (P  < 0.001, P  = 0.006; respectively), and overall bacterial diversity was reduced ( P  = 0.0384) on the skin of malodourous dogs. Staphylococcus and Corynebacterium spp. were not associated with malodour. The topical essential oil‐based product significantly ( P  =   0.0078) improved malodour in the treatment group and shifted their bacterial community structure. Conclusions and clinical importance: A novel association of bacterial genera with malodour in bloodhound dogs, identified by NGS, highlights future targets for odour control. The topical treatment significantly reduced malodour. The interaction between the topical treatment and cutaneous microbiota should be further investigated and may be useful in other dermatological conditions involving microbiota. Abstract : Background – The pathogenesis and treatment of cutaneous malodour in dogs have not been investigated previously. Staphylococcus and Corynebacterium spp. are associated with human axillary malodour.Hypothesis – Staphylococcus and Corynebacterium spp. are associated with cutaneous malodour in dogs, and treatment with a topical essential oil‐based product will improve malodour and reduce the abundance of odour‐causing bacteria.Conclusions and clinical importance – Next‐generation sequencing identified a novel association of bacterial genera with malodour in bloodhound dogs which may serve as future targets for odour control. The topical treatment significantly reduced malodour. The interaction between the topical treatment and cutaneous microbiota should be further investigated and may be useful in other dermatological conditions involving microbiota.